Towards IHE profiles for e-supply in the healthcare domain - Schneider, Gerd; Heidenreich, Georg; Van De Sand, Lasse; Teixeira, Jose; Rathmer, Alfons; Böckmann, Britta; Otten, Hubert; Bergh, Björn; Thun, Sylvia (E-Health - for continuity of care, 2014)
Procurement and supply belong to the crucial supporting processes in hospitals. By providing the right products at the right time in the right quantity in the right place, these processes are of major importance for patient safety and the success of the primary hospital process cure and care. Though of such an importance, the hospital's internal and external procurement and supply processes are still not performed seamlessly by information systems, due to a variety of electronic standards for procurement and supply. These different standards and missing guidelines for electronic procurement and supply in the healthcare domain lead to little or no interoperability between the participating procurement and supply systems. Consequences can be delayed or wrong supply, and increased costs. To overcome this deficiency this work describes the derivation of a common guideline for the implementation of electronically enabled supply processes in the healthcare domain based upon the identification of commonly used electronic standards and detailed specifications of procurement processes in hospital facilities.
Gesehen am 16.02.2021